Structural geology algorithms vectors and tensors - Allmendinger, Richard Waldron (Cambridge University Press, 2012)
"Structural Geology has been taught, largely unchanged, for the last 50 years or more. The lecture part of most courses introduces students to concepts such as stress and strain, as well as more descriptive material like fault and fold terminology. The lab part of the course usually focuses on practical problem solving, mostly traditional me-thods for describing quantitatively the geometry of structures. While the lecture may introduce advanced concepts such as tensors, the lab commonly trains the student to use a combination of graphical methods like orthographic or spherical projection, as well as a variety of plane trigonometry solutions to various problems. This leads to a disconnect between lecture concepts that require a very precise understanding of coor-dinate systems (e.g., tensors) and lab methods that appear to have no common spatial or mathematical foundation. Students have no chance to understand that, for example, seemingly unconnected constructions like down-plunge projections and Mohr circles share a common mathematical heritage: they are both graphical representations of coordinate transformations"--